1998
DOI: 10.1021/bi9723966
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zinc in the Structure and Toxic Activity of Botulinum Neurotoxin

Abstract: Zn2+-protease activity of botulinum neurotoxin causes the blockage of neurotransmitter release resulting in botulism disease. We have investigated the role of Zn2+ in the biological activity of type A botulinum neurotoxin by removing the bound Zn2+ by EDTA treatment, followed by monitoring its structure in terms of secondary and tertiary folding (second derivative UV, FT-IR, and circular dichroism spectroscopy) and function in terms of its effect on the release of norepinephrine from PC12 cells. The single Zn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 33 publications
5
51
1
2
Order By: Relevance
“…In contrast to the EDTA effect, the Zn 2ϩ -specific chelator N,N,NЈ,NЈ-tetrakis (2-pyridylmethyl) ethylenediamine (TPEN) reversibly inhibits the BoNTs in both assays. The results presented here rectify an apparent contradiction between previous reports in which separate studies examined either EDTA or TPEN, leading to opposite results and different interpretations (15,27,33,46). The current data allow the coexistence of the competing observations and suggest that the discrepancies were due to different model systems and different reaction conditions employed in each study.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…In contrast to the EDTA effect, the Zn 2ϩ -specific chelator N,N,NЈ,NЈ-tetrakis (2-pyridylmethyl) ethylenediamine (TPEN) reversibly inhibits the BoNTs in both assays. The results presented here rectify an apparent contradiction between previous reports in which separate studies examined either EDTA or TPEN, leading to opposite results and different interpretations (15,27,33,46). The current data allow the coexistence of the competing observations and suggest that the discrepancies were due to different model systems and different reaction conditions employed in each study.…”
contrasting
confidence: 52%
“…In contrast, the BoNT/E LC required longer incubation with TPEN-at least 60 min to achieve total inhibition. Therefore, extracellular BoNT/E seemed EDTA has previously been shown to physically denature the tertiary structure of BoNT/A, which was attributed to removal of Zn 2ϩ (15,27). When 65 Zn 2ϩ was used, the binding was shown to be reversible but the conformational changes to the LC were not corrected upon reacquisition of 65 Zn 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This involved the use of soluble and immobilized chelators. One of the soluble chelators, EDTA, was the same as that used by Fu et al (9), but the results were profoundly different. In the hands of the present investigators, both EDTA and TPEN caused virtually complete loss of enzyme activity as measured by the cleavage of recombinant substrate.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Fu et al (9) have published findings that seem to contradict those just described. They found that the use of a chelator to remove Zn 2ϩ from toxin led to irreversible changes in tertiary structure as measured by various light-scattering techniques.…”
mentioning
confidence: 88%